Improve Students' Cognitive Ability: The Influence of Two Stay Two Stray Learning Model Assisted by Google Sites - Kurniawati, Evi; Mawarni, Agrintya Indah; Ardianto, Dimas (Proceedings International Conference on Education Innovation and Social Science, 2023)
Evaluation is the final step in determining the success of the learning process. One of them is to evaluate students' cognitive ability after the learning process. This paper will outline students' cognitive ability in Geography classroom employing Two Stay Two Stray learning model assisted by google sites as learning process. In order to improve students' cognitive ability, this research administered classroom action research approach with using test. Interesting me, students showed high difference average value in the last cycle that is 84,82. This increase can be seen from the results of student tests, students are more active and enthusiastic than before also. This improvement caused by Two Stay Two Stray learning model assisted by google sites. They feel difference atmosphere of learning. The Google site as a teaching media also supports students in utilizing technology in an appropriate manner. So, the next researcher must be utilizing technology and modifying learning models so it can be enhance motivation because students' willingness to learn is very influence students' cognitive ability.